NSCA's essentials of training special populations - Jacobs, Patrick L. 1955- (Human Kinetics, 2018)
This volume helps exercise professionals design customised programmes for clients with special conditions and needs. It's also the ideal resource for those seeking to become a National Strength and Conditioning Association (NSCA) Certified Special Population Specialist (CSPS). The text discusses the benefits of exercise for clients with special conditions and the exercise-related challenges they often face. Also, there are details on the importance of safe and effective health and fitness assessments for these clients. Throughout the text, there are a number of learning aids. These come in the form of chapter objectives, study questions, key terms and extra recommended reading.